The multidisciplinary management of median diastema - Alam, Mohammad Khurshed (Bangladesh Journal of Medical Science, 2010)
Maxillary midline diastemas are a common esthetic problem that dentists must treat. Many innovative therapies have been used, varying from restorative procedures to surgery (frenectomies) and orthodontics. The importance of the presence of a maxillary midline diastema resides in its position and the concern it causes to patients. This specific diastema has been attributed to genetic and environmental factors, even though it is often a normal feature of growth, especially in primary and mixed dentition. The need for treatment is mainly attributed to esthetic and psychological reasons, rather than functional ones. Although it is often the case, treatment plans should not be selected empirically but rather should be based on adequate scientific documentation. This paper reviews different treatment techniques to manage the situation and presents three cases to illustrate a range of restorative, prosthetic and orthodontic options. Keywords: Midline diastema; dental spacing; etiology; treatment; relapse. DOI: 10.3329/bjms.v9i4.6691 Bangladesh Journal of Medical Science Vol.09 No.4 July 2010 pp.234-237